A Mobile VR Tool for Vestibular Therapy - Da Silva, Rogerio Eduardo; Dharas, Mahdiyya; Finney, James; Landry, Jacque Pierre (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Visual vertigo is a particular symptom that occurs due to disorders that affect the balance organs in the inner ear (the vestibular system). A treatment option for dizziness and vertigo is vestibular rehabilitation therapy (VRT). This is physical therapy that involves exercising the head, eyes, ears to improve balance and reduce dizziness. In this project we explore the utilization of virtual reality (VR) as a means to provide a simulated environment where patients would be asked to perform a series of vestibular exercises whilst immersed in a controlled virtual environment.